Seven novel HLA alleles reflect different mechanisms involved in the evolution of HLA diversity: description of the new alleles and review of the literature - Adamek, Martina Maria; Klages, Cornelia; Bauer, Manuela; Kudlek, Evelina; Drechsler, Alina; Leuser, Birte; Scherer, Sabine; Opelz, Gerhard; Tran, Thuong Hien (Human immunology, 2015)
The human leukocyte antigen (HLA) loci are among the most polymorphic genes in the human genome. The diversity of these genes is thought to be generated by different mechanisms including point mutation, gene conversion and crossing-over. During routine HLA typing, we discovered seven novel HLA alleles which were probably generated by different evolutionary mechanisms. HLA-B*41:21, HLA-DQB1*02:10 and HLA-DQA1*01:12 likely emerged from the common alleles of their groups by point mutations, all of which caused non-synonymous amino acid substitutions. In contrast, a deletion of one nucleotide leading to a frame shift with subsequent generation of a stop codon is responsible for the appearance of a null allele, HLA-A*01:123N. Whereas HLA-B*35:231 and HLA-B*53:31 were probably products of intralocus gene conversion between HLA-B alleles, HLA-C*07:294 presumably evolved by interlocus gene conversion between an HLA-C and an HLA-B allele. Our analysis of these novel alleles illustrates the different mechanisms which may have contributed to the evolution of HLA polymorphism.
Available online: 11 December 2014
Gesehen am 23.09.2020